Enhancing graduates' employability through polytechnic–industry collaboration. Issue 5 (October 2022) - Otache, Innocent
The unemployability of many Nigerian graduates is somewhat attributable to the existing wide collaboration gap between Nigerian higher education institutions and industry. Against this backdrop, this study explores how Nigerian polytechnics and industry can collaborate to enhance graduates' employability. Adopting a focus group discussion approach, three focus groups involving 20 people (eight polytechnic lecturers, six National Board for Technical Education officials and six industry executives) participated in the study. Content analysis of the focus group discussions revealed the need to involve industry experts in curriculum development and review to meet today's job requirements in industry. The need to involve industry experts in teaching certain aspects of the curriculum was also highlighted. The findings further revealed the desirability of exposing students and lecturers to industrial work situations to equip them with workplace skills and experience. Additionally, the study found that a comprehensive collaboration policy framework, funding, commitment, mutual benefits and trust are required to achieve successful polytechnic–industry collaboration. This research demonstrates that effective collaboration between polytechnics and industry will help to improve the employability of graduates. The findings provide policy and practical implications for polytechnics, regulatory bodies, industry and government.